Plasma Combustion Characteristics of Resistance and Non-Resistance Spark Plugs in a Constant Volume Combustion Chamber (CVCC) - Choi, Yonghyun; Hwang, Joonsik; Kim, Kwonse (International journal of automotive technology, 2023)
This research work is attempted to investigate the internal combustion characteristics which include combustion events using CH 4 gases in a constant volume combustion chamber (CVCC). To visualize the flame event, the experiment via a high-speed camera shows the snapshot through quartz of internal walls. CH 4 gases mixed with air are entered into a chamber via a mass flow controller. The ceramic capacitor is used to apply a plasma effect that can amplify the ignition spark in terms of current amperage. The specification of experimental compositions is set as 400 cc combustion chamber size, 1000 fps high speed camera, 15 ∼ 25 kV spark coil, 0.2 J amplified energy, 1000:1 high voltage probe, 0 ∼ 160 bar pressure sensor, 0 ∼ 15 l/m MFC, 150 bar check valve, and 12.5 V battery. Particularly, the maximum pressure of combustion is highly increased by 1 bar in a plasma plug model. As to an exhaust gas result, CO 2 and NO x in a plasma plug model are partially increased rather than in a conventional plug model. On the other hand, CO and HC are shown that in a conventional plug model, exhaust gas amount is increased than in a plasma plug model.